Complete mitochondrial genome of Stenopsyche tienmushanensis (Trichoptera: Stenopsychidae) - Hu, Yaping (Mitochondrial DNA B Resour, 2021)
The complete mitochondrial genome (mitogenome) of Stenopsyche tienmushanensis Hwang, 1957 was assembled from Illumina high-throughput sequencing data. The circularized mitogenome has a length of 16,049 bp with a high A + T content of 77.9%, including 13 protein-coding genes (PCGs), 22 tRNA genes, and 2 rRNA genes. Its gene composition and order were the same as Stenopsyche angustata. The overall base composition is 42.0% for A, 35.9% for T, 7.6% for C, and 14.5% for G. A phylogenetic analysis based on 13 PCGs of S. tienmushanensis and 20 other caddisflies supports the placement of Stenopsychidae as sister to the Hydropsychidae within Trichoptera.